Flowering behavior and selection of hybrid potato clones through LXT breeding approaches - Amin, Md. Nurul; Rahman, Md. Mushfiqur; Rahman, Mosaddiqur; Al Mahmud, Abdullah; Naznin, Afroz; Islam, Md. Mazadul; Kundu, Bimal Chandra; Alsuhaibani, Amnah Mohammed; Gaber, Ahmed; Ahmed, Sharif (MDPI, 2022)
Potato breeding in Bangladesh is very challenging because it is grown in the short winter season, and flowering does not occur naturally, explaining why artificial lighting and extra care are needed. In addition, the breeding scheme is mainly focused on improving potato yield, followed by tuber quality. The goal of this study was to choose male parents, as well as the effect of environment, on flowering and fruit (berry) setting and to estimate the combining ability among promising BARI-released potato varieties in the second filial generation. Lines of seven Bangladesh Agricultural Research Institute (BARI) varieties were crossed with two BARI variety potato parents as the tester (Line × tester). The BARI Alu-86, BARI Alu-72, BARI Alu-73, and BARI Alu-53 were selected as the best male parents based on the abundance of pollen and fruit set. In both years, flower initiation days varied among clones. For the majority of the traits, such as plant height, tuber number, and yield per plant, the variance of general combining ability (GCA) and specific combining ability (SCA) varied. The inheritance of the considered trait was predominant by non-additive gene action. Concerning general combining ability, for plant height, parents ‘BARI Alu-41’ and ‘BARI Alu-53’, for stem per hill, ‘BARI Alu-79′, for tuber number, ‘BARI Alu-37’, and for yield, ‘BARI Alu-37’ and ‘BARI Alu-79’ contributed complementary favorable alleles. The specific combining ability indicated ‘BARI Alu-37’ × ‘BARI Alu-86’ and ‘BARI Alu-77’ × ‘BARI Alu-72’ were the best potential hybrid families for the production of improved genotypes of tuber yield and tuber number. This study will help to design a breeding program following potato population development and the selection of progeny before their utilization as progenitors.